PORFIRIA ERITROPOETIK KONGENITAL: STUDI KASUS DI LOMBOK - Yunita Hapsari; Dinie Ramdhani K (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2022)
Introduction: porphyria is a group of disorders caused by enzyme deficiency in heme synthesis pathway. Congenital erythropoietic porphyria (CEP) is an extremely rare cutaneous porphyria caused by mutations in the gene encoding uroporphyrinogen III synthase leading to accumulation of porphyrins in erythrocytes and tissues such as skin, teeth and bone resulting in hemolytic anemia, photosensitivity and erythrodontia. Case: we present two cases of CEP with typical manifestation of blistering neonatal-onset photosensitivity, erythrodontia and red-colored urine, as well as one case with hemolytic anemia. Both had no prior history of acute neurological episodes or abdominal pain that establish the cutaneous porphyria diagnosis. Pink fluorescence was visible on the teeth and urine under the Wood's lamp. Further investigations were not conducted. Discussion: the diagnosis of CEP can be established on its typical clinical manifestations and simple investigations with Wood's lamp, confirmed by examination of urine and feces porphyrins, identification of UROS or X-linked GATA 1 gene mutations. CEP management is in the form of comprehensive photoprotection and treatment with various disciplines because the clinical manifestations and severity of CEP vary in each patient. Early age of onset and severity of haematological symptoms are factors that determine poor prognosis. Keywords: congenital erythropoietic porphyria, bullous porphyria, cutaneous porphyria, uroporphyrinogen III synthase.